"Add It to the Parking Lot": Safe Patient Handling and Mobility in the Emergency Department. Issue 3 (July 2018) - Havey, Renee; Aebersold, Cassandra; Terrasi, Jason
Abstract : Nelson and Baptiste noted that a standard approach to safe patient handling and mobility (SPHM) cannot be generalized to all patient care areas because the unique, high-risk tasks of each area require specific intervention. Matching the SPHM program to the setting, tasks, and roles is important in developing a program that will prevent harm. However, there is little evidence related to the use of SPHM programs in nontraditional care environments, such as emergency departments (EDs). A such, there is no standardized method for training ED nurses in safe patient handling. An SPHM challenge unique to the ED is extricating patients out of vehicles. There are several ways to extricate patients from vehicles, with some requiring more resources, people, and equipment than others. These resources vary depending on the patient's level of activity and acuity. The purpose of this article is to articulate the importance of SPHM programs in EDs and the unique challenges and workflows that complicate implementation in this chaotic environment through a review of manual and equipment-assisted methods of extricating patients from the vehicle.